HIV-related stigma among young men who have sex with men in HIV care in Plateau State Nigeria - Afolaranmi, Tolulope O.; Chaplin, Beth; Zoakah, Ayuba I.; Kanki, Phyllis J. (Frontiers in Public Health, 2025)
BackgroundHIV-related stigma is often expressed as irrational behaviors, negative attitudes, and unfavorable judgments toward people living with or at risk of HIV which remains very common in low- and middle-income countries including Nigeria. This study assessed the level of HIV-related stigma and its associated factors among Young Men who have Sex with Men (YMSM) in HIV care.MethodologyThis was a cross-sectional study conducted among 122 YMSM to assess the level of HIV-related stigma and its associated factors among YMSM in HIV care using respondent driven sampling between July 2023 and April 2024. Quantitative method of data collection was employed and SPSS version 23 was used for data analysis. A p-value of ≤ 0.05 was considered statistically significant.ResultsThe mean age of the study participants was 22.2 ± 2.0 years with 56 (45.6%) being 22 years and below. The total HIV- related stigma score for the participants was 121.9 ± 18.8 with high-level of stigma reported among 40 (32.8%) of the participants. Significant variation in the mean total HIV-related stigma score was found with duration on HIV treatment with those who had been on treatment for >3 years having a mean score of 117.8 ± 15.2 compared to 110.3 ± 20.1 for those who had been on treatment for <2 years (mean difference: −7.50; 95% Confidence interval: −14.45, −5.51; p = 0.035).ConclusionThis study found a high level of HIV-related stigma among the YMSM in HIV care which is significantly influenced by the duration of time in HIV care.